2018
DOI: 10.1177/0898264318806390
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perception of Physicians and Medication Adherence Among Older Adults With Hypertension

Abstract: Objective: To assess association between patient perception of physicians and adherence to antihypertensive medication among Medicare beneficiaries. Method: Logistic regression was used to assess association between the Patient Perception of Physicians Scale score and adherence to antihypertensive medication. The 2007 Medicare Current Beneficiary Survey data were used to create a 12-item patient perception of physician scale and 2008 Medicare Part D claims to assess adherence. Results: There were 2,510 benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Seven of the included studies reported a consistent trend: a higher number of prescribed hypertensive medications correlated with lower medication adherence. 13,16,20,23,24,28,29 This aligns with robust evidence from a nationwide study conducted in the Republic of Korea, which aimed to investigate the impact of the number of medications and age on antihypertensive medication adherence. The study demonstrated a significant decline in adherence when nine or more total medications were taken, irrespective of age.…”
Section: Discussionsupporting
confidence: 57%
“…Seven of the included studies reported a consistent trend: a higher number of prescribed hypertensive medications correlated with lower medication adherence. 13,16,20,23,24,28,29 This aligns with robust evidence from a nationwide study conducted in the Republic of Korea, which aimed to investigate the impact of the number of medications and age on antihypertensive medication adherence. The study demonstrated a significant decline in adherence when nine or more total medications were taken, irrespective of age.…”
Section: Discussionsupporting
confidence: 57%
“…[ 28 ] (2020) reported that patient–provider relationship had a positive effect on Black cancer survivors’ health outcomes, especially when they had a positive perception of quality care from their doctor. Furthermore, Ward and Thomas (2020)[ 25 ] found evidence that positive patient perceptions of their physicians were associated with greater adherence to hypertension medication. We found that Medicare beneficiaries with more positive perceptions of their doctors were more likely to speak to them about experiencing UI compared to those with less favorable perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Questions that were negatively worded, such as “Your doctor seems to be in a hurry,” “Your doctor often does not explain your medical problems to you,” and “Your doctor often acts as though he/she was doing you a favor by talking to you,” were reverse-coded, whereby “4” indicated strongly disagree, “3” indicated disagree, “2” indicated agree, and “1” indicated strongly agree. All values were summed to produce a “patient perception of physician scale.”[ 25 ] Higher scores were indicative of more positive perceptions of the physicians.…”
Section: Methodsmentioning
confidence: 99%
“…The interviews revealed the willingness of patients to participate in the project and some of their preferences. As shown in Table 2, they wish to control blood pressure, presumably because they experience this noninvasive manouvre during medical examinations [15], and prefer to discuss their health problems with their doctor, as in our clinic they spend more time talking with physicians than other professionals [16]. In terms of benefits expected of an AmI environment, women preferred to receive advice on nutrition but did not ask for specific information.…”
Section: Discussionmentioning
confidence: 99%